Demographic model and biological adaptation inferred from the genome‐wide single nucleotide polymorphism data reveal tripartite origins of southernmost Chinese Huis. Issue 3 (4th December 2022) - He, Guanglin; Fan, Zhi‐Quan; Zou, Xing; Deng, Xiaohui; Yeh, Hui‐Yuan; Wang, Zheng; Liu, Jing; Xu, Quyi; Chen, Ling; Deng, Xiao‐Hua; Wang, Chuan‐Chao; Liu, Changhui; et al.
Abstract: Objectives: The culturally unique Sanya Hui (SYH) people are considered descendants of ancient Cham people in Central Vietnam and exhibit a scenario of complex migration and admixture history. We aimed to characterize the genetic structure, origin, and admixture history of SYH people and explore the effect of the cultural admixture from Central/South Asia and East Asia on their genetic admixture. Materials and Methods: We sampled 94 Hui individuals from Hainan and genotyped these samples using the Infinium Global Screening Array version 2 with over 717K SNPs. We then investigated the demographic history of SYH people by combining currently available modern and ancient genome‐wide SNP data and leveraging shared allele‐ and haplotype‐based strategies. Results: Patterns of genetic differentiation showed that SYH people were genetically different from the northern Hui but harbored a close genomic affinity with indigenous Vietnamese. SYH had a relatively distant relationship with the Cham, which confirmed the hypothesis of the documented recent historical migration from Central Vietnam and assimilation with the Hainan indigenous people. The fitted three‐way admixture models and the reconstructed demographic frameworks showed that SYH was the admixture result with primary ancestry from East Asia and mainland Southeast Asia and minor ancestry related to Central/South Asia. GLOBETTRTER and ALDER‐based admixture time estimation revealed that genetic contact with Central Asia occurred around 28 generations ago. Our model was consistent with the frequent cultural communication along the Southern Maritime Silk Road and extensive interaction with East Asia. Besides, analyses focused on natural‐selected signatures of SYH people revealed some candidate loci associated with metabolism and immune function. Discussion: The SYH people are considered to be Cham refugees' descendants. A long‐standing hypothesis posits that SYH derives from different genetic and cultural origins, which hypothesizes that the genetically attested admixture history of SYH people is different from northern Hui people possessing prominent Han‐related ancestry and minor western Eurasian ancestry. We found that the genetic structure of SYH people was different from Vietnam Cham and geographically diverse Hui people. Generally, three genetically attested genealogies from Central Vietnam, East Asia, and Central/South Asia in modern SYH people supported their tripartite model of genomic origins. Abstract : Patterns of genetic differentiation showed that SYH people were genetically different from the northern Hui but harbored a close genomic affinity with indigenous Vietnamese. SYH had a relatively distant relationship with the Cham, which confirmed the hypothesis of the documented recent historical migration from Central Vietnam and assimilation with the Hainan indigenous people. The fitted three‐way admixture models and the reconstructed demographic frameworks showed that SYH was the admixture result with primary ancestry from East Asia and mainland Southeast Asia and minor ancestry related to Central/South Asia. GLOBETTRTER and ALDER‐based admixture time estimation revealed that genetic contact with Central Asia occurred around 28 generations ago. Our model was consistent with the frequent cultural communication along the Southern Maritime Silk Road and extensive interaction with East Asia. Besides, analyses focused on natural‐selected signatures of SYH people revealed some candidate loci associated with metabolism and immune function.